2014
DOI: 10.1088/0029-5515/54/5/054002
|View full text |Cite
|
Sign up to set email alerts
|

Laser–plasma interactions for fast ignition

Abstract: In the electron-driven fast-ignition (FI) approach to inertial confinement fusion, petawatt laser pulses are required to generate MeV electrons that deposit several tens of kilojoules in the compressed core of an imploded DT shell. We review recent progress in the understanding of intense laser–plasma interactions (LPI) relevant to FI. Increases in computational and modelling capabilities, as well as algorithmic developments have led to enhancement in our ability to perform multi-dimensional particle-in-cell s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 129 publications
1
47
0
1
Order By: Relevance
“…Recent simulations for similar laser and plasma conditions confirm that indeed the most energetic electrons originate in the underdense plasma region. 31 A comparison to the experimental electron temperature results is shown in Fig. 5.…”
Section: Electron Productionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent simulations for similar laser and plasma conditions confirm that indeed the most energetic electrons originate in the underdense plasma region. 31 A comparison to the experimental electron temperature results is shown in Fig. 5.…”
Section: Electron Productionmentioning
confidence: 95%
“…33 Near the critical density (defined as the density above which the laser does not propagate) acceleration occurs predominantly through the J Â B mechanism, leading to the so-called ponderomotive scaling 29 of T e as a function of the local laser intensity, I (in W cm À2 ): T e % 0:511 Â ð ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi 1 þ Ik 2 =1:4 Â 10 18 q À 1Þ (MeV), where k is the laser wavelength in lm. In the under-dense region of the plasma, primarily produced via ablation from the laser prepulse, electron acceleration occurs due to stochastic processes 31 and T e is given by 30 …”
Section: Electron Productionmentioning
confidence: 99%
“…[204,93,207,81,5,9,177,152,88] Yet, the bulk of research to date has indicated that electrons generated by a petawatt laser at an optically-thick interface do not naturally exhibit collinear trajectories with respect to the laser propagation axis, but rather substantial divergences. This has been shown with some clarity in experiment and through kinetic numerical simulations, but the primary underlying cause has eluded a clear description.…”
Section: 5mentioning
confidence: 99%
“…Other promising tracks of research have focused on understanding the initial absorption in detail; that is, the processes controlling the conversion of the ignitor laser energy into electron energy [86,152,88,72,163,175,62,83,106,109] . Germane research of this latter Figure 1.5 : Overview of the physics involved in the coupling of the ignitor pulse energy to the imploding DT fuel.…”
Section: 5mentioning
confidence: 99%
“…In electron-driven fast ignition (EFI), a fast electron jet generated by ultra-high intensity lasers triggers ignition of the thermonuclear fuel. Due to the very large divergences and the too high kinetic energies found in EFI experiments and simulations [2,3], ion-driven fast ignition (IFI) has been taking an increasing interest over the last years. Ion fast ignition [4,5] offers several advantages over EFI, such as generation of collimated beams, well known interaction with the plasma and higher flexibility.…”
Section: Introductionmentioning
confidence: 99%